(untitled) (Transport systems and technologies, 2023)
Basalt fiber is a promising material that can be used to create a new class of building materials. It has a number of advantages, including high strength, low weight and resistance to chemicals. One of the disadvantages of basalt fiber is its low alkali resistance. In an alkaline environment, the fiber is destroyed, which limits its use in building materials exposed to alkalis. The paper investigates the effect of heat treatment on the alkali resistance of basalt fiber. It was found that heat treatment at a temperature of 500 0C increases the alkali resistance of the fiber by 80%. This is due to the compaction of the fiber structure and the formation of iron-oxygen tetrahedra on its surface, which are resistant to alkalis. The authors of the article substantiate the feasibility of using heat-treated basalt fiber in transport construction. This material can be used to manufacture new types of building materials that are resistant to alkalis.